Self-reported health literacy and medication adherence in older adults: a systematic review - Corinna Bergelt; Moritz Sebastian Schönfeld; Stefanie Pfisterer-Heise (BMJ Open)
Objectives To give an overview over the associations between self-reported health literacy and medication adherence in older adults.Design A systematic literature review of quantitative studies published in English and German.Data sources MEDLINE via PubMed, CINAHL, Cochrane Library, Epistemonikos and LIVIVO were searched.Eligibility criteria Included studies had to examine the associations between self-reported health literacy and medication adherence in the elderly (samples including ≥66% of ≥60 years old) and had to use a quantitative methodology and had to be written in English or German.Data extraction and synthesis All studies were screened for inclusion criteria by two independent reviewers. A narrative synthesis was applied to analyse all included studies thematically. Quality assessment was conducted using the NIH Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies.Results We found 2313 studies, of which nine publications from eight studies were included in this review. Five studies reported a majority of participants with limited health literacy, one study reported a majority of participants with adequate health literacy, and three publications from two studies only reported mean levels of health literacy. Eight publications from seven studies used self-reports to measure medication adherence, while one study used the medication possession ratio. Overall, six publications from five studies reported significantly positive associations between health literacy and medication adherence while two studies reported positive but non-significant associations between both constructs and one study reported mixed results.Conclusion In this review, associations between self-reported health literacy and medication adherence are rather consistent, indicating positive associations between both constructs in older adults. However, concepts and measures of health literacy and medication adherence applied in the included studies still show a noteworthy amount of heterogeneity (eg, different use of cutoffs). These results reveal the need for more differentiated research in this area.PROSPERO registration number CRD42019141028.